Pengaruh Literasi Keuangan Dan Mindset Entrepreneur Terhadap Kinerja UMKM Di Pasar Alok Maumere - Arnoldus Arianto; Wilhelmina Mitan; EmilianusEo Kutu Goo (Jurnal Mutiara Ilmu Akuntansi, 2023)
This study aimed to determine the effect of financial literacy and entrepreneurial mindset on the performance of Micro, Small, and Medium Enterprises ( MSMEs). This research employed a quantitative approach. The population in this study was 630 MSME players in the Alok market, Maumere. The sample was selected using the solvin formula resulting in 87 respondents. The data used in this study was primary data. The data were collected using questionnaires distributed to MSME players in the Alok market. The data were analyzed using descriptive statistical analysis, data qality test, multiple linear regression analysis, t-test, F test with the assisst of IBM SPSS, coefficient of determination. The results of this study indicated that partially and simultaneously financial literacy and entrepreneurial mindset had no effect on the performance of MSMEs in the Alok market, Maumere.